Shading Reciprocal Motion and Directional Continuous Filling of Dielectric Liquids in Photovoltaic LN‐based Sandwich Structures - Liu, Xiaohu; Wang, Cheng; Shi, Lihong; Wang, Mengtong; Huai, Zechao; Li, Chenyu; Zhang, Lina; Wang, Xuan; Yan, Wenbo (Laser & photonics reviews, 2025)
A challenge faced by photovoltaic microfluidic manipulation for biochemical reactions or drug synthesis is how to avoid direct laser irradiation of microfluids that usually causes photo‐damage on various photosensitive targets. Herein, by creating photovoltaic‐charge paths on LiNbO 3 (LN)‐based sandwich structures through laser pre‐scanning, this study achieves shading reciprocal motion and directional continuous filling of dielectric liquids along laser pre‐scanning paths. It compares the microfluidic behaviors in two types (LN/LN and LN/Glass) of sandwich structures and propose an interfacial photovoltaic‐charge transfer and combination mechanism, where the negative charges on one LN surface of the sandwich structure transfer to the other LN surface with a lower electric potential through the liquid/air interface and recombine with the positive charges there. By utilizing this shading mode of microfluidic manipulation in LN/LN structure, the safe delivery of fluorescent dyes and fragile particles that are subject to photobleaching and photodegradation effects is achieved, respectively. Moreover, it finds that the interfacial charge transfer in the LN/Glass structure is significantly suppressed, thereby minimizing the break of the liquid filling lines and allowing for the directional continuous filling of complex patterns (1D/2D) in a shading mode. The outcome paves the way for the development of future LN‐based biochemical photonic microfluidic platforms.